2016
DOI: 10.1002/hbm.23106
|View full text |Cite
|
Sign up to set email alerts
|

FMRI of spinal and supra‐spinal correlates of temporal pain summation in fibromyalgia patients

Abstract: Fibromyalgia syndrome (FM) is a debilitating chronic pain condition, which afflicts primarily females. Although the etiology of this illness is not completely understood, FM pain is thought to rely on enhanced pain sensitivity maintained by central mechanisms. One of these mechanisms is central pain amplification, which is characterized by altered temporal summation of second pain (TSSP). Here we use a TSSP paradigm and functional MRI (fMRI) of the spinal cord, brainstem, and brain to non-invasively examine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
102
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(113 citation statements)
references
References 46 publications
8
102
0
3
Order By: Relevance
“…12 The present study found that PAS, which were prominent in subjects with FM, and more rare in control subjects, were associated with differences in MTL response (specifically, deactivation). Of note, MTL alterations have been previously reported in FM.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…12 The present study found that PAS, which were prominent in subjects with FM, and more rare in control subjects, were associated with differences in MTL response (specifically, deactivation). Of note, MTL alterations have been previously reported in FM.…”
Section: Discussionsupporting
confidence: 49%
“…67 Importantly, a handful of studies have shown that PAS are more pronounced in FM patients than in control subjects. 12,62,70,72 Additionally, PAS appear to be more closely correlated to pain severity than other QST measures, including indices of temporal summation, 2,65,73 underlining their potential clinical relevance. Whereas PAS have been studied by several groups psychophysically, their associated brain activity has not been investigated.…”
mentioning
confidence: 95%
“…Coordinated responses have also been demonstrated between brainstem and spinal cord regions in response to noxious heat stimuli, mechanical hyperalgesia, and stimulation to induce temporal summation of pain in healthy and fibromyalgia syndrome study groups. SEM analyses have further demonstrated brainstem and spinal cord networks in both healthy participants and people with spinal cord injuries [23, 2933]. The coordinated responses to noxious stimuli in these studies provide evidence of responses to stimuli as well as descending modulation of the spinal cord.…”
Section: Discussionmentioning
confidence: 91%
“…However we did not implement this experimental design because of the difficulty in applying matched perceived electrical stimulus to the anaesthetised rodent. An earlier study found evidence for altered descending pain control mechanisms in FM sufferers by measuring differential BOLD responses in the spine and brainstem relative to normal controls42. Our fMRI sequence did not capture these regions which may merit future investigation given the findings by Bosma et al .,42.…”
Section: Discussionmentioning
confidence: 86%
“…An earlier study found evidence for altered descending pain control mechanisms in FM sufferers by measuring differential BOLD responses in the spine and brainstem relative to normal controls42. Our fMRI sequence did not capture these regions which may merit future investigation given the findings by Bosma et al .,42. There is evidence that FM patients also exhibit altered temporal BOLD response profiles43 and examination of this property in the RIM model would represent an interesting extension of this work, though beyond the scope of the current investigation.…”
Section: Discussionmentioning
confidence: 99%